PENGUKURAN EFEKTIFITAS DAN EFISIENSI, KONTRIBUSI SERTA PERTUMBUHAN RETRIBUSI PAJAK TERHADAP PAD DI KOTA PALEMBANG - Trie Sartika Pratiwi; . Padriyansyah; Dessy Dwi Anggraini (Jurnal RATRI (Riset Akuntansi Tridinanti), 2021)
ABSTRACK The results of this study revealed that (1) the contribution of parking retribution revenue toward the Regional Generated Revenue (RGR) from 2013 to 2015 tended to improve. The improvement of its contribution occurred in 2013 was 1,47%, in 2015 was 1,40%, but it decreased to be 0,11% in 2014. (2)The effectiveness of parking retribution acceptance in Palembang in 2013 was 83.43%, 87,30% in 2014, and 92,70% in 2015. Thus, the revenue of parking retribution in Palembang during 2013, 2014, and 2015 was not effective. Mean while, the parking retribution revenue was effective enough in 2015. It was because its effectiveness around 100% while the efficiency of parking retribution revenue in Palembang was 26,32% in 2013, 25,16% in 2014, and 21,56% in 2016. Thus, the revenue of parking retribution in Palembang ran efficiently because the efficiency achieved was under 100%. (3)The growth of parking retribution revenue in Palembang from 2013 to 2015 was positive. The amount of growth was 20.33% in 2014, in 2013 the growth of parking retribution revenue was negative (8.21%). It means that the revenue of parking retribution in 2015 decreased to be 6.18% from the previous year. Keywords : contribution, effectiveness, efficiency, parking retribution